THE EXISTENCE OF MUSLIM-FRIENDLY KOS TREND IN MALANG CITY: DO THE PEOPLE OF MALANG REJECT INTOLERANCE?: CASE STUDY IN MERJOSARI VILLAGE, MALANG CITY - Holikul Mubin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This study examines the phenomenon of the existence of Muslim/Muslimah-exclusive boarding houses in Merjosari Village, Malang City. The research aims to explore and understand the underlying reasons for the presence of the "Accepting Muslim/Muslimah Tenants" label in several boarding houses within the area. Utilizing a qualitative approach with interview and observation methods, the results reveal that this phenomenon is not intended to discriminate against non-Muslim individuals, but rather serves as an effort by boarding house owners to maintain a religious and social environment aligned with prevailing norms. Furthermore, the study identifies previous traumatic experiences among some boarding house owners when renting to non-Muslim tenants, such as behavior that contradicts the local values and norms. This research is expected to contribute to the formulation of policies by the government, educational institutions, and the community regarding more inclusive accommodation options, as well as to promote a better understanding and realization of tolerance within the social environment.